The African Continental Free Trade Area (Afcfta): A Bold Attempt at Trade Liberalization in Africa - Nagu, Yakubu; Nkannebe, Raymond (ABUAD Private and Business Law Journal, 2018)
This paper examines the prospects and challenges of the African Continental Free Trade Area (AfCFTA) initiative. Africa is at an extraordinary point in history, one in which a global decline in fertility ratesis being experienced. In Africa, unlike the rest of the world, births outnumber deaths four to one. Within the next 30 years, Africa will be home to the largest population of young people in the world, and by the year 2100, a third of the global labour force will be African. These demographic changes are instructive. Africa must seize the opportunities that come with an increasingly dynamic market space, or its 2063 Agenda of transformation may elude it. The African Continental Free Trade Area (AfCFTA) initiative was formulated as a reaction to this. This paper evaluates the African Continental Free Trade Area and its significance to the broader conversation on the Continent’s development. The paper also examines the ‘development integration model, upon which the AfCFTA initiative is based and appraises the legal agreement creating the it along with its supporting protocols on goods, services and dispute settlement. It goes on to consider the Initiative’s prospects with regards to economic growth and development on the Continent and examines challenges likely to bedevil its operation. In the paper, it is argued that optimizing the benefits of the AfCFTA will require a broad perspective as well as coherent development policies driven by ambitious and transformational leadership.